2006
DOI: 10.1097/00006199-200607000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Perineal Dermatitis in Nursing Home Residents

Abstract: Several correlates of perineal dermatitis (mechanical chafing, fecal and double incontinence, and use of restraints) appear modifiable through nursing intervention. Clinical interventions should consider the complex health status of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
1
16

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 23 publications
6
89
1
16
Order By: Relevance
“…The first World Continence Week (June [22][23][24][25][26][27][28]2009) sponsored by the International Continence Society 31 is one example of coordinating global awareness of incontinence and showcasing the scientific and clinical contributions of multidisciplinary professionals. As urinary and fecal incontinence occur concurrently in many patients, 32,33 there is an unexploited potential for collaborative research on awareness and prevention of both conditions, which have been investigated separately for the most part.…”
Section: Increasing Awareness Of Fecal Incontinence Continence Literacymentioning
confidence: 99%
“…The first World Continence Week (June [22][23][24][25][26][27][28]2009) sponsored by the International Continence Society 31 is one example of coordinating global awareness of incontinence and showcasing the scientific and clinical contributions of multidisciplinary professionals. As urinary and fecal incontinence occur concurrently in many patients, 32,33 there is an unexploited potential for collaborative research on awareness and prevention of both conditions, which have been investigated separately for the most part.…”
Section: Increasing Awareness Of Fecal Incontinence Continence Literacymentioning
confidence: 99%
“…The model was originally developed for a study of PD in hospital patients, but Bliss et al (2006) saw a potential use for guiding analysis of PD in nursing home residents. They added the use of restraints as an indicator of toileting ability because of its high relevance to nursing home residents and operationalized its components using the MDS after the analysis described in this study was completed.…”
Section: Variablesmentioning
confidence: 99%
“…Yet, few studies about PD or its associated factors in older adults in any setting have been conducted. Bliss, Savik, Harms, Fan, and Wyman (2006) investigated the prevalence and correlates of PD in nursing home residents, guided by a conceptual model of PD (Brown & Sears, 1993). Minimum Data Set (MDS) items were used to represent the factors in the model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In health care settings, most skin maceration is related to incontinence. It has been reported that urinary and/ or fecal incontinence is prevalent in more than half of nursing home residents [5] and in 28% of elderly people living at home [6]. The prevalence of incontinence is higher in the elderly [6,7], who also comprise a population with skin vulnerabilities due to senescence [8].…”
Section: Introductionmentioning
confidence: 99%